2006
DOI: 10.17763/haer.76.1.e14543458r811864
|View full text |Cite
|
Sign up to set email alerts
|

(In)Fidelity: What the Resistance of New Teachers Reveals about Professional Principles and Prescriptive Educational Policies

Abstract: In this article, Betty Achinstein and Rodney Ogawa examine the experiences of two new teachers who resisted mandated "fidelity" to Open Court literacy instruction in California. These two case studies challenge the portrayal of teacher resistance as driven by psychological deficiency and propose instead that teachers engage in "principled resistance" informed by professional principles. They document that within prescriptive instructional programs and control-oriented educational policies, teachers have a limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
148
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(156 citation statements)
references
References 2 publications
5
148
0
3
Order By: Relevance
“…In seeking to provide a relevant and authentic SBHE, the teachers unproblematically described the modifications they made to the Health Literacy @ Ipswich Schools curriculum package. Here we see evidence of the earlier noted alignment tensions between fidelity and contemporary teaching and learning principles (Achinstein and Ogawa 2006). For example, the Bluemarine SHS leader provided the following insight:…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…In seeking to provide a relevant and authentic SBHE, the teachers unproblematically described the modifications they made to the Health Literacy @ Ipswich Schools curriculum package. Here we see evidence of the earlier noted alignment tensions between fidelity and contemporary teaching and learning principles (Achinstein and Ogawa 2006). For example, the Bluemarine SHS leader provided the following insight:…”
mentioning
confidence: 59%
“…Increasingly, such concerns have drawn attention to notions of poor fidelity of program implementation, whereby the implementation of an evidence-based health intervention in school settings fails to match the original design conditions and protocols (Ennett et al 2011;Dusenbury et al 2003). This emphasis on fidelity however, has been questioned by education and health scholars who have suggested that intentional adaptations may not be counterproductive and strict adherence to fidelity may compromise and suppress teachers' capacity to enact the principles of their profession (Achinstein and Ogawa 2006;O'Donnell 2008). In this paper we directly engage with this conundrum to demonstrate the limitations of employing public health notions of fidelity within the education system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the majority of them did not approve of the substantial reductions in content load and tended to supplement it with direct teaching due to concerns with students' academic success, nationwide examinations, the increasing demand for private tutoring and deepening educational inequalities. These teachers therefore demonstrated principled resistance (Achinstein et al 2006), since they perceived curriculum change proposals as detrimental to their students and to society in general.…”
Section: Implementation Challengesmentioning
confidence: 99%